2016
DOI: 10.1016/j.eats.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Reduction and Internal Fixation for Pipkin Type I Femoral Head Fracture: Technical Note

Abstract: Femoral head fractures after posterior dislocation of the hip are uncommon and are conventionally treated by an open method. Hip arthroscopy can be a valuable treatment option for the management of femoral head fractures. Arthroscopy allows for a less invasive option when compared with arthrotomy and can allow faster recovery with minimal soft-tissue injury. We describe the arthroscopic reduction and internal fixation of Pipkin type I femoral head fractures with a detailed stepwise description of the surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Many investigators agree that hip arthroscopy is useful in treating the intra-articular lesions (namely, loose bodies, labral tears, chondral lesions) documented in radiological exams after traumatic hip dislocation in order to prevent further complications. 11 , 12 , 13 , 14 Some (Mullis and Dahners) go further to say that a routine hip arthroscopy should be done after traumatic hip dislocation, as intraoperative loose bodies can be found in patients in which standard radiographic studies found no loose bodies and a concentric reduction was obtained. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Many investigators agree that hip arthroscopy is useful in treating the intra-articular lesions (namely, loose bodies, labral tears, chondral lesions) documented in radiological exams after traumatic hip dislocation in order to prevent further complications. 11 , 12 , 13 , 14 Some (Mullis and Dahners) go further to say that a routine hip arthroscopy should be done after traumatic hip dislocation, as intraoperative loose bodies can be found in patients in which standard radiographic studies found no loose bodies and a concentric reduction was obtained. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Eight articles were included 21,[28][29][30][31][32][33][34] . Of the evaluated articles, five were retrospective case reports (Level V) and three were case series studies (Level IV).…”
Section: Study Settingmentioning
confidence: 99%
“…Hip arthroscopy has gained increasing popularity for the management of various hip disorders, in particular femora-acetabular impingement, in recent years. 50 Its role in the management of fractures of the femoral head, however, is largely unexplored, with only a few case reports in the literature and no long-term follow-up results. 51 , 52 In a technical note, Kekatpure et al 50 provided a stepwise description for the arthroscopic reduction and internal fixation of Pipkin type I femoral head fractures.…”
Section: Definitive Treatmentmentioning
confidence: 99%
“… 50 Its role in the management of fractures of the femoral head, however, is largely unexplored, with only a few case reports in the literature and no long-term follow-up results. 51 , 52 In a technical note, Kekatpure et al 50 provided a stepwise description for the arthroscopic reduction and internal fixation of Pipkin type I femoral head fractures. This technique showed acceptable reduction with maintained joint space, and may thus represent an alternative to the usually performed open reduction with the advantages of minimal surgical soft tissue injury and early rehabilitation in posttraumatic cases.…”
Section: Definitive Treatmentmentioning
confidence: 99%
See 1 more Smart Citation